We free the stars - Faizal, Hafsah (Sands of Arawiya, 2021)
In a world inspired by ancient Arabia, seventeen-year-old Zafira and the sultan's son Nasir continue their quest to uncover a lost magic artifact and discover that the prize they seek may be even more dangerous than any of their enemies.